2012
DOI: 10.1186/1472-6882-12-207
|View full text |Cite
|
Sign up to set email alerts
|

Current status of Kampo medicine curricula in all Japanese medical schools

Abstract: BackgroundThere have been a few but not precise surveys of the current status of traditional Japanese Kampo education at medical schools in Japan. Our aim was to identify problems and suggest solutions for a standardized Kampo educational model for all medical schools throughout Japan.MethodsWe surveyed all 80 medical schools in Japan regarding eight items related to teaching or studying Kampo medicine: (1) the number of class meetings, target school year(s), and type of classes; (2) presence or absence of ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…To address this issue, we established a validation set consisting of all fourth-year MS at the two different medical universities who had been blinded to the three common questions and had taken each Web-based test after KM education in 2016. Various differences have been reported in the number and length of KM education classes, in the presence or absence of full-time KM instructors, and in the content of the curricula and textbooks used for KM education between Japanese medical universities and colleges [5]. In the present study, MS at university B had significantly more correct answers to the three common questions than MS at university A ( Table 3).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…To address this issue, we established a validation set consisting of all fourth-year MS at the two different medical universities who had been blinded to the three common questions and had taken each Web-based test after KM education in 2016. Various differences have been reported in the number and length of KM education classes, in the presence or absence of full-time KM instructors, and in the content of the curricula and textbooks used for KM education between Japanese medical universities and colleges [5]. In the present study, MS at university B had significantly more correct answers to the three common questions than MS at university A ( Table 3).…”
Section: Discussionmentioning
confidence: 41%
“…Various differences have been reported in the number and length of KM education classes, in the presence or absence of full‐time KM instructors, and in the content of the curricula and textbooks used for KM education between Japanese medical universities and colleges . In the present study, MS at university B had significantly more correct answers to the three common questions than MS at university A (Table ).…”
Section: Discussionmentioning
confidence: 46%
“…Those factors, in turn, might have led to ‘Lack of CAM education’. In fact, ‘Lack of CAM education’ is the case in the curricula of medical schools in Japan .…”
Section: Discussionmentioning
confidence: 99%
“…In the 2011 survey of Arai et al (2012), two universities reported no Kampo classes in the curriculum; one university was on the road to a new curriculum, while in the other university, Kampo was offered in liberal arts and science courses. Accordingly, Kampo medicine was incorporated into the medical curriculum at the 78 medical schools (98% of the 80 medical schools) in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the number of compulsory Kampo-related classes during the six years of medical school have been reported to range between 0 and 25, with a median of 6 classes (Arai et al 2012). In the 2011 survey of Arai et al (2012), two universities reported no Kampo classes in the curriculum; one university was on the road to a new curriculum, while in the other university, Kampo was offered in liberal arts and science courses.…”
Section: Discussionmentioning
confidence: 99%